The Future of Philippine Agriculture under a Changing Climate Policies, Investments and Scenarios - Rosegrant, Mark W. 1950-; Agcaoili-Sombilla, Mercedita C. (ISEAS Publishing, 2019)
The Philippine economy has grown rapidly since 2010, but despite this growth, poverty and inequality remain high. Two-thirds of the poor live in rural areas, and the weak performance of the agriculture sector has contributed to the slow improvement in livelihoods. The challenge for agriculture will further increase, with climate change posing a growing threat to the sector. But agricultural transformation to spur sustained growth and reduce poverty is still possible under climate change with aggressive institutional reforms and implementation of the right mix of policies and programmes. The identification of the suitable policy and programme combination requires an accurate assessment of the key drivers of agricultural growth and food security; the impacts of climate change on agriculture and the overall economy; and the effectiveness of policies for adaptation and growth.